Unpacking spatial planning as the governance of place. Extracting potentials for future advancements in planning research. - Schmitt, Peter; Wiechmann, Thorsten (Taylor & Francis, 2018)
Since the 1990s, the concept of governance has become an integral element of spatial planning research. In this article, we revisit some of the key contributions to the literature to discuss how and to what extent governance theory has informed planning theory so far and what the implications are for our understanding of how to construe planning practices. Next, we examine the current governance literature in order to identify promising elements that can further inform planning theory and practice. More specifically, we discuss relations between hybrid modes of governance in regard to cross-sectoral coordination of actors and institutions, and the implications of various forms of learning within governance networks. Finally, we suggest entry points for planning research such as studying the combination and interplay of various modes of governance to understand the inherent functioning of spatial planning assemblages, or investigating the learning capacity of actors and institutions in order to anticipate their adaptive capacity to respond to changing contexts in spatial planning practice. However, we also point out a few, yet troublesome implications. One of them is that planning understood as the governance of place might imply that the term "planning" as such becomes meaningless and that planning theory might turn into a subsection of (institutional) political theory. The article serves as a framing text for this special issue as it addresses a number of key elements and underlying concepts of the governance literature that are relevant for understanding the procedural dimension of spatial planning and which underpin some of the issues that are addressed in the more case study-based contributions by the other authors.
Keywords: Planungstheorie; Planungsforschung; Stadtplanung; Regionalplanung; Raumbezug; Ort; Planungsgeschichte; Governance; Akteur; Kooperation; Planungsbeteiligung; Planungsprozess; Planungsorganisation; Veränderung; Entwicklungspotenzial